ROLE OF HIGH CHOLESTEROL AND HIGH FAT DIET ON LIPID PROFILES IN SPRAGUE DAWLEY RATS - . Yanuartono (Jurnal Sain Veteriner, 2007)
Fourty five-male Sprague Dawley rats, weighing about 100g of 2 month old were used as experimental animals to studyt he role of high cholesterol and high fat diets on blood lipid profiles, triglyceride, HDL, LDL, and total cholesterol. Before this research began, rats were adapted for a week and were fed basal diet. The rats were then randomly alloted into three groups( I, II, UI) of 15 each. Group I as control was fed normal (basal) diet, group II was fed diet containing high fat diet, and group III was fed diet containing high cholesterol and high fat diet. After 3, 6, and 12 weeks on experimental diets, blood specimen from 5 rats of each group were collected to determine triglyceride, HDL, LDL, and total cholesterol concenhation. The statistic alanalyses using multifactorial randomized design for blood lipid, showed that experimentat time periods caused significant increase(p <0.05) in the total cholesterol concentration, wish, 1 2 weeks on experimental diet was the highest concentration. Diet and experimental time periods showed significant increase(p <0.05) in the total triglyceride concentrations,a fter 12 weeks of treatments was the highest concentration. Significantly increased( p<0.05) in HDl-cholesterol concentrations were caused by diet and experimental time periods, however, there was no significant effect by interaction between experimental time periods and diet. Significantly increased (p<0.05) inLDL-cholesterol concentrations were caused by diet and experimental time periods. However, there was no interaction between experimental time periods and diets in total LDL-cholesterol concentration. In this study,high fat and high cholesterol d iet group (group III) and six weeksi n experimental diet had the greatest influenced in total LDL-cholesterol concentration. Based upon the experimental results, it can be concluded that: (l) high cholesterol and high fat diet could increase total cholestrol concentration and total triglyceride concentration, (2) there was no interaction between experimental time periods and diet on HDL-cholesterol and LDL-cholesterol concentration.Key words: Sprague Dawley rats, triglyceride, HDL, LDL, and cholesterol